Mediating effects of inequitable gender norms on intimate partner violence and contraceptive use in a cluster randomized control trial in Niger - Boyce, Sabrina C; Minnis, Alexandra M; Deardorff, Julianna; McCoy, Sandra I; Goin, Dana E; Challa, Sneha; Johns, Nicole E; Aliou, Sani; Brooks, Mohamad I; Nouhou, Abdoul-Moumouni; Baker, Holly; Silverman, Jay G (American journal of epidemiology, 2025)
Previous research has demonstrated that the Reaching Married Adolescents intervention (RMA) was associated with changes in inequitable gender norms, intimate partner violence (IPV), and modern contraceptive use. This study seeks to understand if changes in inequitable gender norms mediate the RMA intervention's effects on contraceptive use and intimate partner violence (IPV). A 4-arm cluster randomized control trial was conducted to evaluate effects of the RMA intervention (household visits, small groups, combination, control) on married adolescent girls and their husbands in Dosso, Niger (baseline: 1042 dyads; 24 months follow-up: 737 dyads; 2016-2019). Mediation was assessed using inverse odds ratio weighting. In the small group intervention, of the total effect on IPV prevalence (8% reduction), indirect effects via inequitable gender norms are associated with a 2% decrease (95% CI, -0.07 to 0.12) and direct effects with a 6% decrease (95% CI, -0.20 to -0.02). For household visits, of the total effect on contraceptive use (20% increase), the indirect effect accounts for an 11% decrease (95% CI, -0.18 to -0.01) and direct effect, a 32% increase (95% CI, 0.13-0.44); this is similar to findings for the combination arm. This experimental evidence informs the value of changing underlying social norms to reduce IPV and increase contraception use.